(untitled) (The Planet, 2024)
Introduction: Teachers play a key role in student learning. In all phases of education, student achievement correlates with the quality of teachers. But teacher shortage in basic subjects is a great issue and this crisis is affecting the students as well as the whole medical education system. Aim of the study: This study aimed to assess the views of teachers and students about an acute shortage of teachers of basic subjects in medical colleges in Bangladesh. Methods and materials: This descriptive cross-sectional study spanned from January to December 2021, encompassing four medical colleges in Bangladesh, comprising two governments and two private institutions. The study included 456 participants, with 96 being basic subject teachers in medical colleges and 360 students in the 1st-3rd phases of the MBBS course. Data analysis involved the SPSS version 22.0 program. Result: The study found unanimous concern among teachers (100%) and students (82.22%) regarding a shortage of teachers in basic subjects. Notably, 26.04% of teachers noted shortages in Pharmacology, while 27.1% identified deficiencies in Forensic Medicine and 26.04% in Anatomy. Lack of facilities was cited by 44.8% of teachers as the primary cause. In Pharmacology, 75% of students lacked sufficient teachers, with 88.33% feeling the medical college didn’t meet their teacher needs. Conclusion: The study findings suggest that there is a shortage of teachers of basic subjects in medical colleges in Bangladesh. To address this issue, recommendations from both teachers and students in medical colleges are essential for devising effective solutions to mitigate these challenges.